Pandemi Covid-19: Dampak Global dan Peluang Bagi Sektor Pertanian Indonesia - Paksi, Arie Kusuma; Musyaffa, Nadhif Fadhlan; Iswari, Rani Dian (Intermestic: Journal of International Studies; Vol 7 No 2 (2023), 2023)
The covid-19 pandemic has had a crucial impact on the agricultural sector in the world and in particular the agricultural sector in Indonesia. The purpose of this research is to find out how the impact of the Covid-19 pandemic has had an on the Indonesian agricultural sector and how the Indonesian agricultural sector can adapt to this impact. In this research, the authors used primary data from 2013 to 2022 with data from twelve ministries, institutions, and provincial governments in Indonesia. Also, the author uses secondary data that comes from articles, books, and other credible sources. The author uses an adaptive capacity approach in analyzing the development of the Indonesian agricultural sector in the era of the covid-19 pandemic. Based on the author's qualitative research analysis, the Indonesian agricultural sector can adapt well in the covid-19 pandemic era by having high resilience, as well as anticipated vulnerabilities. Also, the covid-19 pandemic has actually provided the new potential for the Indonesian agricultural sector. The author proposes five initiatives to ensure the long-term sustainability of Indonesia's agricultural sector.